2018
DOI: 10.1002/jper.16-0388
|View full text |Cite
|
Sign up to set email alerts
|

Soft drink consumption and periodontal status in pregnant women

Abstract: Background Periodontal disease is associated with metabolic syndrome, and during pregnancy, it is linked to preeclampsia and preterm birth. We hypothesized that soft drink consumption, which has also been associated with metabolic disorders, may also be linked to periodontal disease. The purpose of this study was to evaluate the association between soft drink consumption and periodontal status in pregnancy. Methods This was a cross‐sectional study nested in BRISA (Brazilian Ribeirão Preto and São Luís Birth Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…First, there have been very few studies on the relationship between soft drinks and periodontal health [20][21][22]. Fann et al reported a frequency-dependent relationship between the intake of soft drinks and periodontal disease in Taiwanese middle-aged adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, there have been very few studies on the relationship between soft drinks and periodontal health [20][21][22]. Fann et al reported a frequency-dependent relationship between the intake of soft drinks and periodontal disease in Taiwanese middle-aged adults.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms linking soft drink intake and periodontal disease could involve the separate or combined effects of oxidative stress or bone mineralization [31][32][33][34][35][36][37]. Associations between heavy soft drink intake and periodontitis may be due to the induction of inflammatory pathways or metabolic syndrome resulting from excess sugar consumption, which has been previously associated with periodontal disease [20,[38][39][40]. However, further studies are needed to verify these potential mechanisms more precisely [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) How many times a day do you take soft drinks? The frequencies of weekly intake (zero to seven days a week) and of daily intake (once to six times a day) of soft drinks reported by the women were multiplied and categorized as a dichotomous variable corresponding to no or low consumption (o7 times per week) or high consumption (X7 times per week) (14). This cutoff point was assumed since the majority of previous studies has shown that daily SSBs intake is associated to worse health outcomes, such as obesity and hypertension (8,9,15).…”
Section: Exposure Variables Confounding Factors Mediators and Outcomementioning
confidence: 99%